Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Xevinapant, an antagonist of inhibitor of apoptosis proteins (IAPs) from the SMAC-mimetic drug class, was developed to restore apoptosis in cancer cells. Preclinical studies demonstrated on-target IAP degradation, caspase activation, and pro-inflammatory apoptosis via TNF-α upregulation. Monotherapy activity was modest in both preclinical and phase I studies, pointing to a primarily synergistic role as a (chemo)radiosensitizer, with the strongest antitumor signals observed in head and neck squamous cell carcinoma (HNSCC). In the Debio1143-201 phase II trial in locally advanced HNSCC, adding xevinapant to chemoradiation dramatically improved locoregional control and suggested favorable long-term survival, raising hopes for the first practice-changing advance in concomitant chemoradiotherapy in two decades. Unexpectedly, the TrilynX phase III trial was definitively negative, showing detrimental effects on survival and greater toxicity, which halted the development of SMAC mimetics as anticancer drugs. High intratumoral drug exposure was confirmed, but supporting pharmacodynamic data were largely derived from indirect pro-apoptotic signals in peripheral blood biomarkers. Here, we review xevinapant's trajectory, highlighting both the promise and risks of apoptosis-directed therapies, and extract key lessons for future oncology drug development by examining existing preclinical evidence, pharmacodynamic biomarkers, trial design and interpretation, and challenges associated with dosing agents that have a narrow therapeutic index.